The influence of emotional intelligence on front-line employees' job performance in service businesses / Abdul Kadir Othman - Othman, Abdul Kadir (2010)
The current study conceptualizes the role of EI dimensions in influencing employees' job performance dimensions by taking into account the moderation effects of service typologies; namely, Professional Service, Service Shop and Mass Service, the nature of service (the extent of Emotional Labor used during service provision), and the employees' differences; which include Personality Traits and Internal Work Motivation in to a cohesive framework. Job performance dimensions were observed from two different standpoints; peer's and supervisor's evaluations. Data were collected from front-line service employees attached to 40 purposively selected service companies located in Selangor and Kuala Lumpur. Questionnaires were distributed through the human resource manager of the participating companies. The process of data collection took approximately six months from October 2007 to March 2008. Out of 400 questionnaires distributed, 188 were returned yielding a response rate of 47%. However, 19 responses were non-usable leaving 167 responses to be analyzed. A series of statistical analyses were applied to test the hypotheses as well as to answer the research questions. The analyses include descriptive analyses, reliability analysis, correlation analysis, factor analysis, and multiple regression analysis. Besides, moderated multiple regression (MMR) for categorical variables were applied to analyze the moderating effects of Service Type variables. A series of hierarchical regression analyses were performed to analyze the moderating effects of Emotional Labor, Personality Traits and Internal Work Motivation.